2019
DOI: 10.25259/sni_176_2019
|View full text |Cite
|
Sign up to set email alerts
|

A challenging case of concurrent multiple sclerosis and anaplastic astrocytoma

Abstract: Background: Cases of gliomas coexisting with multiple sclerosis (MS) have been described over the past few decades. However, due to the complex clinical and radiological traits inherent to both entities, this concurrent phenomenon remains difficult to diagnose. Much has been debated about whether this coexistence is incidental or mirrors a poorly understood neoplastic phenomenon engaging glial cells in the regions of demyelination. Case Description: We present the case of a 41-year-old patient diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In our patient case, the tumefactive lesion is cortical; based on location, it should not have been identified as a TD lesion. Despite diagnostic differences, lack of MRI specificity remains a challenge, especially in the presence of active MS, edema and inflammatory processes [ 29 ]. CT-PET imaging can be utilized to identify malignancies but a confirmatory brain biopsy may be required for patients with overlapping features such as atypical ring-enhancing lesions and mass effect [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient case, the tumefactive lesion is cortical; based on location, it should not have been identified as a TD lesion. Despite diagnostic differences, lack of MRI specificity remains a challenge, especially in the presence of active MS, edema and inflammatory processes [ 29 ]. CT-PET imaging can be utilized to identify malignancies but a confirmatory brain biopsy may be required for patients with overlapping features such as atypical ring-enhancing lesions and mass effect [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas have been reported in patients with multiple sclerosis (MS) 1 , 2 . As immune surveillance is critical in cancer development, a possible causal immuno-genetic relationship between neuroinflammatory diseases and malignant brain tumors has been repeatedly discussed 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Another large study investigated the occurrence of brain tumors in 33 different autoimmune diseases and found that none of them (including MS) influences the risk of glioma development but that autoimmune diseases negatively affect survival in glioma and meningioma patients, probably due to the added physical burden or therapeutic limitations [3]. Accordingly, some of the challenges the clinical management of concurrent CNS tumors and MS pose have been described in the literature but due to the rare coincidence of these two CNS diseases, current evidence is limited to single case reports and, to our best knowledge, no cohort studies have been reported [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%